Pengembangan Sistem Informasi Akademik Sekolah dan Asrama (Studi Kasus : SMA Sulthon Aulia Boarding School) - Miftah Muhammad Farhan; Achmad Arwan; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Sulthon Aulia Boarding School has two curricula, namely the school curriculum and the dormitory curriculum. Students for three years will be educated in an Islamic life education so that is is expected to produce graduates who are faithful and pious, morality, have a soul of leadership, and have an entrepreneurial spirit. But in the process of forming good graduates it is still less efficient. The assessment process still uses conventional methods and has the risk of losing data so that it can slow down the assessment process of students both at school and in the dormitory. Academic information system is a solution to the problems above. Student assessments will be recorded online and will minimize data loss. In developing this system, the development method used is the waterfall method. The development of this system resulted in the elicitation of needs in the form of 5 actors, 42 functional needs and 1 non functional requirement Then from the results of the design produces 5 designs, namely architectural design consisting of sequence diagram design, class diagram design, database design and interface design. Then from the results of the design phase carried out the implementation process that results in the implementation of the interface and algorithm implementation. At the system testing stage, the tests carried out are integration testing, unit testing, validation testing and compatibility testing. Based on the testing that has been done, the results are 100% successful in testing functional requirements. In compatibility testing, the system was tested on different devices and got 100% results successfully.